1994
DOI: 10.1007/bf01986395
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of respiratory burst by tumor necrosis factor in neutrophils adherent to fibronectin. Evidence for a crucial role of CD18 glycoproteins

Abstract: Human neutrophils, plated on fibronectin (FN)-coated wells, were found to release large quantities of superoxide anion (O2-) in response to tumor necrosis factor alpha (TNF-alpha). The O2- release was completely inhibited by two monoclonal antibodies (MoAbs, MHM23 and TS1/18) against CD18 glycoproteins. An independently derived anti-CD18 MoAb (60.3) was ineffective. These MoAbs failed to inhibit neutrophil adhesion to FN-coated surfaces. Moreover, neutrophils incubated for 30 min on FN and then washed to remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…These observations suggest that the modulation of ␤ 2 -integrin via GM-CSF was the mechanism of adhesiondependent EOS functional upregulation. Like VCAM-1, EOS adhesion to fibronectin is not dependent on ␤ 2 -integrin expression, but such adhesion can enhance ␤ 2 -dependent GM-CSF-or TNF-␣-stimulated EOS respiratory burst (57,58). Moreover, Sung and coworkers (59) recently reported that GM-CSF enhances the adhesion strength of EOS and VCAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that the modulation of ␤ 2 -integrin via GM-CSF was the mechanism of adhesiondependent EOS functional upregulation. Like VCAM-1, EOS adhesion to fibronectin is not dependent on ␤ 2 -integrin expression, but such adhesion can enhance ␤ 2 -dependent GM-CSF-or TNF-␣-stimulated EOS respiratory burst (57,58). Moreover, Sung and coworkers (59) recently reported that GM-CSF enhances the adhesion strength of EOS and VCAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome b 558 is localized with CD11b/CD18 in secretory vesicles [142]. In this light, adhesion-dependent enhancement of oxidative burst induced by LPS, TNF, fMLP, or phorbol esters may be due to the mobilization to the membrane of both CD11b/CD18 (Mac-1) and cytochrome b 558 [155][156][157][158]. Indeed, this form of activation may explain both vascular sequestration and the increased oxidant capacity of PMNs during endotoxemia.…”
Section: Pmn Primingmentioning
confidence: 99%
“…Whereas TNF␣ can prime neutrophils in suspension (9, 10), many TNF␣-induced cellular responses, including oxidant release, have been reported in association with ␤ 2 -mediated, integrin-mediated adherence (11)(12)(13). Neutrophils utilize a variety of adhesion molecules (14), but studies employing either genetically manipulated mice (15), antibody blocking studies (16), and studies with adhesion molecule-deficient patients (17) have shown that integrins, in particular ␤ 2 and ␤ 3 , are fundamentally important in adhesive events (16,18).…”
mentioning
confidence: 99%